2017
DOI: 10.22267/rus.171901.70
|View full text |Cite
|
Sign up to set email alerts
|

Situación de caries, gingivitis e higiene oral en gestantes y no gestantes en hospitales del Valle del Cauca, Colombia

Abstract: Introducción: La atención odontológica durante el embarazo es una oportunidad para promover la salud y prevenir la enfermedad bucodental relacionada con complicaciones con el parto. Objetivo: Describir las diferencias o semejanzas en la prevalencia de caries, de gingivitis y la higiene bucodental en gestantes y no gestantes de 13 municipios del Valle del Cauca en Colombia entre el año 2009 y 2011. Materiales y métodos: Se analizó la base de datos del proyecto prioridad salud oral del Valle del Cauca 2009-2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 21 publications
(29 reference statements)
0
15
0
3
Order By: Relevance
“…It is important to eliminate irritating factors, since they increase the epidemiological characteristics of periodontal disease and influence the loss of gingival attachment. 7,15 Other studies report socioeconomic, 5,7,12 and racial 5,13 determinants as factors associated with the presence of gingivitis during pregnancy. We asked about the level of schooling and place of origin, where most of the pregnant women were from rural areas and had no education or even higher education, however, no significant association was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to eliminate irritating factors, since they increase the epidemiological characteristics of periodontal disease and influence the loss of gingival attachment. 7,15 Other studies report socioeconomic, 5,7,12 and racial 5,13 determinants as factors associated with the presence of gingivitis during pregnancy. We asked about the level of schooling and place of origin, where most of the pregnant women were from rural areas and had no education or even higher education, however, no significant association was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In Latin America it affects three quarters of pregnant women attended in hospitals. [12][13][14][15][16] A study carried out in a family medicine unit of the Mexican Social Security Institute in the city of Acapulco, found that the prevalence of biofilm and periodontal disease in pregnant women was 74% and 65%, respectively. 17 It has been found that the etiology of periodontal disease during pregnancy is multicausal.…”
Section: Prevalence Of Gingivitis and Risk Factors Among Pregnant Wom...mentioning
confidence: 99%
See 1 more Smart Citation
“…El granuloma piógeno también conocido como "hemangioma eruptivo", "hemangioma de granulación del tejido tisular", "granuloma gravídico", "hemangioma capilar lobular" y "tumor del embarazo" 29,30 constituye una lesión oral asociada a un sobrecrecimiento de tejido debido a irritación, trauma físico o factores hormonales 10,31 . La gran vascularización presente en las lesiones recientes hacen que clínicamente se presente de color rojo, que cambia a rosa violeta en aquellas más antiguas, lisa o lobulada 32 , puede presentarse como una masa pediculada o sésil con base amplia [17][18][19] .…”
Section: Granuloma Piógenounclassified
“…Los índices de caries dental en embarazadas varían en Latinoamérica dependiendo del país, en Brasil la caries dental en embarazadas llega a 84,9% con un índice CPOD de 4,0 9 ; en Colombia se reporta una prevalencia del 82,8% con índice CPOD del 6,69 10 , en un reporte del 2011 en Cuba se relata una prevalencia del 80,95% de caries en gestantes 11 , que para el 2015 en el mismo país alcanzó el 62,7% con un promedio de índice CPOD de 2,5 12, mientras que en Chile estos valores alcanzan el 37,6% con un índice CPOD de 4,79 13 .…”
Section: Introductionunclassified